153 Fracture risk estimation with FRAX®: is the bone mineral density test necessary?. (8th June 2022) - Kraut, Roni; Ding, Mao; Babenko, Oksana
Abstract : Objectives: Fractures can have a devastating impact on the function of older adults, and population-based screening is recommended by many organizations to help prevent fractures. The Fracture Risk Assessment tool (FRAX®) is a validated, widely used, 12-question tool to predict 10-year fracture risk and can be calculated with or without bone mineral density (BMD) results. FRAX without BMD results has been shown to be a valid screening tool; yet, to our knowledge, there has not been a Canadian study based in primary care providing such evidence. The objectives of our study were to 1) determine the difference in risk estimates using FRAX with BMD and FRAX without BMD, and 2) assess the direct cost of BMD. Method: Retrospective chart review. Patients between the ages of 50–74 affiliated with a primary care clinic in Edmonton, Canada were eligible if they 1) had a BMD completed by Medical Imaging Consultants from 2017–2022; and 2) did not have a prescription for a bisphosphonate at the time of the BMD. The on-line FRAX calculator for Canada was used to calculate the risk of major osteoporotic fracture, and this risk was then categorized as low (<10%), moderate (10%-20%), or high (>20%). The variables for the FRAX calculation were extracted from BMD reports and patients' charts. The direct cost (physician billing) was calculated using the Alberta Medical Association health service code X128. Results: There were 90 eligible patients. The median age was 65 years old (interquartile range [IQR] 58–67); 98% (n = 88) were female; 6% (n = 5) had a previous fragility fracture; 10% (n = 9) had a parent with a hip fracture; 3% (n = 3) were smoking tobacco; 1% (n = 1) were positive for exposure to oral glucocorticoids; 0% (n = 0) had a disorder that favored secondary osteoporosis; 0% (n = 0) imbibed ≥3 units of alcohol daily; and the median femoral neck t-score was -1.3 (IQR -1.95 to - 0.5). Risk estimates using FRAX with and without BMD were concordant for 86% of patients (n = 77):72% (n = 65) had low risk and 13% (n = 12) had moderate risk of fracture. Risk estimates were discordant for 14% of patients (n = 13): 12% (n = 11) had discordance in the low-moderate risk classification; 1% (n = 1) had discordance in the moderate-high risk classification; and 1% (n = 1) had discordance in the low-high risk classification. The median risk difference in the discordance scores was 4% (IQR 3.1%-4.5%). The total cost of physician billings for BMD was $12, 764. Conclusions: For most patients affiliated with this primary care clinic, using the FRAX tool without BMD did not change the risk classification of future fracture risk but resulted in additional costs. Further, most of the discordance revolved around the low-to-moderate risk classification, which is less likely to change clinical management per Osteoporosis Canada guidelines. These results are consistent with other studies that have found including BMD in the FRAX tool may not be necessary for fracture screening.